2014
DOI: 10.18357/ijcyfs.bookml.5412014
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Narrative Processes With Children and Young People

Abstract: This article focuses on the photo-narrative research process with children and young people. The photo-narrative method invites children and young people to answer research questions by first taking photographs and then talking to the researcher about them. We reflect critically on our own photo-narrative study by asking such questions as: In what ways can the photo-narrative method be seen as a participative method? How were the various power relations between the child and the researcher actualized? What met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Informed consent was freely given (on two occasions by each informant), and was also updated during the research process, especially where photographs were concerned. The researchers went through every photograph selected by the informant, who made the decision to allow or not allow use of the photograph in question (Böök & Mykkänen, 2014;Mykkänen & Böök, 2013). Throughout the research process, we treated informants' consent as an ongoing process and open to review at all times (Einarsdóttir, 2007).…”
Section: Datamentioning
confidence: 99%
“…Informed consent was freely given (on two occasions by each informant), and was also updated during the research process, especially where photographs were concerned. The researchers went through every photograph selected by the informant, who made the decision to allow or not allow use of the photograph in question (Böök & Mykkänen, 2014;Mykkänen & Böök, 2013). Throughout the research process, we treated informants' consent as an ongoing process and open to review at all times (Einarsdóttir, 2007).…”
Section: Datamentioning
confidence: 99%
“…Kirk (2007) argues using photos as a central aspect in an interview with a child can serve to lessen the power imbalance between the researcher and the child (see also Kaplan, 2013). The primary attention of the interviews is then on the images children create and their articulation of what those photos mean to them (Böök and Mykkänen, 2014). Certainly, the differences in control between the researcher and child participants are not completely diminished using photography or any other method employed by adult researchers (James, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, we found that poor picture quality did not limit the information obtained when we asked children what they intended to show us. A photo, even one that is blurry or an image the child had not intended, still provided a focal point (see also Böök and Mykkänen, 2014: 617).…”
Section: Methodsmentioning
confidence: 99%
“…Wang, as well as other researchers, emphasizes that the group discussion stage is the most important moment of photovoice (Wang et al, 1998;Böök, Mykkänen, 2014). Presenting photographs and talking about them is conducive to critical reflection, both on individual situation as well as on the whole community.…”
Section: Photovoice Processmentioning
confidence: 97%
“…Photovoice is a flexible method that can be easily applied to various research topics and a wide spectrum of social problems (Wang, Burris, 1997). Previous research projects using photovoice have been conducted, among others, with children and teenagers (Clark-Ibanez, 2007;Böök, Mykkänen, 2014),women (McIntyre, 2003, people with disabilities (Dassah et al, 2017), homeless people (Miller, 2006), prostitutes, members of ethnic, religious or cultural minorities (Finney, Rishbeth, 2006), people discriminated against on the basis of gender identity, as well as people with mental health problems (Clements, 2012). These examples show the value of photovoice in recognizing the specificity of many social groups and different problems (Grieblinget al, 2013).…”
Section: Social Work and Photovoicementioning
confidence: 99%